Etične dileme pri uporabi in oskrbi oseb z zmanjšano zmožnostjo s podporno tehnologijo - Moharić, Metka (Rehabilitacija (Ljubljana), 2017)
Assistive technology (AT) is any product, equipment or technology adapted or specially designed for improving the functioning of a person with disability. While there are numerous potential benefits of AT, there are also a number of ethical issues. The four major principles of medical ethics also apply to the use and provision of AT: autonomy, beneficience, non-maleficience and justice. Justice is the principle with which we deal the most often. AT is among the measures that can ensure certain basic human rights. Ethical solutions to problems are rarely straightforward. Thorough thought is required in AT implementation in order not to limit the individual or trespass his/her rights.
Keywords: assistive technology; človekove pravice; Disabled Persons; ethical issues; ethics; etične dileme; human rights; medical aids; medical device; medicinski pripomočki; podporna tehnologija; rehabilitation; Self-Help Devices